UPAYA MENINGKATKAN SIKAP PERCAYA DIRI DAN PRESTASI BELAJAR IPA MATERI PENGARUH PERUBAHAN LINGKUNGAN FISIK TERHADAP DARATAN MELALUI MODEL PEMBELAJARAN QUANTUM - Susanti, Susi (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2019)
The student’s low self-confidence and learning achievement became the main problem in class IV SD Negeri 2 Sudagaran Banyumas. Some factors causing the low confidence and learning achievement were that the learning was still conventional; the students were not active during the lesson. The research was conducted as the solution using quantum learning model. This was a classroom action research with two cycles consisting of planning, acting, observing, and reflecting. The result of the research showed that quantum learning model could improve the student’s confidence and learning achievement for the fourth graders of SD Negeri 2 Sudagaran Banyumas. It could be proven by the improvement of the student’s questionnaire got improvement, it was 73,48 % in cycle I on in enough criteria and 77,28% in cycle II or in good criteria. The result of the students’ learning mastery also got improvement, it was 78,27% in cycle I or in good criteria and 86,96% in cycle II or in very good criteria. Based on the result of this classroom action research conducted in two cycles, it could be concluded that quantum learning model could improve the students’ confidence and learning achievement on science on the topic of The Effect of Physically Environment change for the fourth graders of SD Negeri 2 Sudagaran Banyumas.